Association Between Adiponectin Levels with Markers of Atherosclerosis In Patients with Rheumatoid Arthritis - Tanggo Meriza; Harry Isbagio; Rahmad Mulyadi; Murdani Abdullah (Indonesian Journal of Rheumatology, 2014)
Background: Several studies have shown that atherosclerosis underlying processes of Cardiovascular disease (CVD), increased in rheumatoid arthritis (RA) and occurred early (premature). The cause of accelerated atherosclerosis in RA are still unknown.Adipokines have known that the adipokines play a role in the pathophysiology of RA and CVD. Accumulation of visceral fat associated with dysregulation of adipokinesthat influence the development of the atherosclerotic and disruption plaque. Obesity and pathological changes in fat mass and fat dysfunction as well as a change inthe pattern of secretion of proinflammatory adipokines, may have a correlation between heart disease and rheumatic diseases. Adiponectin is one of the mostwidely-studied adipokines. In RA, adiponectin is involved in the pathophysiology of RA that produces of various proinflammatory and prodestructive molecules. So far, adiponectin has been known to provide antiatherosclerotic effects in patients with non-RA. But, several recent studies in RA patients get opposite results in which increased levels of adiponectin are associated with increased prevalence of atherosclerosis. The effect of adiponectin on atherosclerosis in patient with RA is still unknown.Objective: to determine the relationship of adiponectin with atherosclerosis in patients with rheumatoid arthritis. Methods: This is a cross-sectional study conducted on outpatients of the rheumatology clinic at Cipto Mangunkusumo General Hospital from January untilApril, 2013. Subjects consisted of 50 patients were diagnosed based on ACR 1987/EULAR 2010 criteria. The collection of data obtained by consecutive sampling and evaluated the patients’ medical data that included age, long-suffering of RA, body mass index (BMI), lipid profile, rheumatoid factor levels, levels of anti-cyclic citrullinated peptide (anti-CCP), C-reactive protein (CRP), erythrocyte sedimentation rates (ESR), blood pressure, fasting blood glucose, 2 hour post prandial blood glucose, ECG, examination of serum adiponectin levels and bilateral carotid ultrasound to measure the carotid artery intima media thickness.Results: From the results of the 50 patients studied, obtained 28 (56%) of patients had increased levels of adiponectin. Atherosclerosis was found in 13 (26%) subjects. The median value was 9.46 μg / ml with the lowest levels of 4 μg/ml and the highestlevels of 24μg/ml. The Spearman’s test showed no significant correlation between adiponectin serum and atherosclerosis in patients with RA (p = 0706 and r = 0.055). The analysis results of the correlation of adiponectin with atherosclerosis based on age, disease duration, ESR, rheumatoid factor, DAS 28, CRP, BMI, dyslipidemia showed no significant correlation.Conclusion : From this study, researchers found no statistically significant correlation between adiponectin levels with marker of atherosclerosis (CIMT) in patients with rheumatoid arthritisKeywords : Adiponectin, Atherosclerosis